The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.05.28.493840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Investigation of the YidC-Mediated Membrane Insertion of Pf3 Coat Protein Using Molecular Dynamics Simulations

Abstract: YidC is a membrane protein that facilitates the insertion of newly synthesized proteins into lipid membranes. Through YidC, proteins are inserted into the lipid bilayer via the SecYEG-dependent complex. Additionally, YidC functions as a chaperone in protein folding processes. Several studies have provided evidence of its independent insertion mechanism. However, the mechanistic details of the YidC independent protein insertion mechanism remain elusive at the molecular level. This study elucidates the insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Previous studies have revealed that the YidC transmembrane (TM) region is crucial for membrane protein insertion mechanism 19,75,76 . In order to examine the impact of deleting the PD and C2 loop on the TM helices, the helical angle between each pair of TMs was measured in this work (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have revealed that the YidC transmembrane (TM) region is crucial for membrane protein insertion mechanism 19,75,76 . In order to examine the impact of deleting the PD and C2 loop on the TM helices, the helical angle between each pair of TMs was measured in this work (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Å. The interhelical angles were determined as the angle between the third main axes of the respective helices 19,60,67,70,71 . The selection of the TM helices and other sub-domains are as indicated: TM1 (355-388); TM2 (423-442); TM3 (466-479); TM4 (497-508); TM5 (511-528);…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations